1991
DOI: 10.1111/j.1474-919x.1991.tb04590.x
|View full text |Cite
|
Sign up to set email alerts
|

The daily pattern of autumn bird migration in the northern Sahara

Abstract: The temporal pattern of migration by passerine birds during the night, and their arrival during the day at the Egyptian coast and in the northern Sahara Desert was investigated. The mean direction of nocturnal migration at the coast was south-southeast, while at all desert sites it was south-southwest.Birds arrived at the Egyptian coast only during the second half of the night which is explained by the fact that n o birds could have taken off from the Mediterranean Sea. At least some of the birds landed at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 14 publications
3
14
1
Order By: Relevance
“…Moving further south and east in the eastern desert and across the Nile Valley, the density of migration at the northern part of the western Red Sea coast in Hurghada is higher than in Sharm El Shiekh and along the Nile Valley and western desert in Fayoum, which confirms the results of Kiepenheuer and Linsenmair (1965), Biebach et al (1991) and Bruderer (2001).…”
Section: Migration Intensitysupporting
confidence: 80%
See 1 more Smart Citation
“…Moving further south and east in the eastern desert and across the Nile Valley, the density of migration at the northern part of the western Red Sea coast in Hurghada is higher than in Sharm El Shiekh and along the Nile Valley and western desert in Fayoum, which confirms the results of Kiepenheuer and Linsenmair (1965), Biebach et al (1991) and Bruderer (2001).…”
Section: Migration Intensitysupporting
confidence: 80%
“…However, the migration intensity at the western Mediterranean coast in Egypt is little known, there is an obvious decrease in migration intensity from north to south along the Nile Valley and the Red Sea Coast and the higher intensity of migration in the eastern Egypt than in the western part. This is also confirmed by Biebach et al (1991), Bruderer and Liechti (1995) and Bruderer (2001).…”
Section: Migration Intensitysupporting
confidence: 74%
“…Furthermore, numbers of birds found in the desert during daytime were regarded as being comparatively low compared to the total number of migrants estimated by Moreau (Wood 1989). This non-stop hypothesis was challenged by Bairlein (1985Bairlein ( , 1992 and Biebach et al (1986Biebach et al ( , 1991 who proposed an alternative intermittent strategy that involves regular stopovers in the desert and in oases. The main argument for an intermittent migration strategy was that an unexpectedly high proportion of passerines grounded in oases were in good physical condition with sufficient fuel stores to continue migration (Bairlein et al 1983;Bairlein 1992;Biebach 1995).…”
Section: Introductionmentioning
confidence: 99%
“…This means that under good weather condition (tail wind at high altitudes) all species make a non-stop flight, whereas under bad weather condition (head winds at high altitudes) some species make the intermittent and others non-stop flight. Biebach et al (1991) studied the daily pattern of autumn bird migration in the northern Sahara, where the temporal pattern of migration by passerine birds during the night and their arrival during the day at the Egyptian coast and in the northern Sahara Desert was investigated. A correlation between the number of migrants observed during the night and the number of resting birds in the desert on the following day suggested that an unknown proportion of birds might have regularly used the intermittent migratory strategy that included stopover periods during day when crossing the desert, whereas others might have adapted the non-stop migratory strategy.…”
Section: Passerines' Migration Strategies Across the Mediterranean Anmentioning
confidence: 99%
“…During four migratory seasons from 1980 to 1985, H. Biebach and his colleagues of the Max-Planck Institute fr Verhalternsphysiologie studied bird migration in Bahariya oases. This work was particularly useful in illustrating the species composition and behavioural strategies of birds crossing the Egyptian portion of Sahara (Biebach 1985(Biebach , 1988(Biebach , 1990(Biebach , 1992(Biebach , 1996Biebach et al 1986;Biebach et al 1991;Biebach et al 2000).…”
Section: Introductionmentioning
confidence: 99%